Deltex acts as a positive regulator of Notch signaling through interactions with the Notch ankyrin repeats. - Matsuno, K.; Diederich, R.J.; Go, M.J.; Blaumueller, C.M.; Artavanis-Tsakonas, S. (Development, 1995)
We present a molecular and genetic analysis which elucidates the role of deltex in the Notch signaling pathway. Using the yeast 'interaction trap' assay, we define the protein regions responsible for heterotypic interactions between Deltex and the intracellular domain of Notch as well as uncover homotypic interaction among Deltex molecules. The function of the Deltex-Notch interaction domains is examined by in vivo expression studies. Taken together, data from overexpression of Deltex fragments and from studies of physical interactions between Deltex and Notch, suggest that Deltex positively regulates the Notch pathway through interactions with the Notch ankyrin repeats. Experiments involving cell cultures indicate that the Deltex-Notch interaction prevents the cytoplasmic retention of the Suppressor of Hairless protein, which otherwise is sequestered in the cytoplasm via association with the Notch ankyrin repeats and translocates to the nucleus when Notch binds to its ligand Delta. On the basis of these findings, we propose a model wherein Deltex regulates Notch activity by antagonizing the interaction between Notch and Suppressor of Hairless.